The stance of Uday bin Hatim from the political developments in the Rashidi period - Omerah, Bader Haif (Journal of Humanities & Social Sciences, 2023)
This study deals with talking about the position of Uday bin Hatim from the political events in the Rashidi era, most notably the apostasy events that followed the death of the Messenger of God, and the start of the Islamic conquest movement, then the strife that swept the Islamic state at the end of the era of the Rightly-Guided Caliphate Perhaps in this research we revealed the positive impact of Uday bin Hatim’s firm position on Islam, as well as in containing the positions of his tribe’s branches, unifying their position and directing them in the interest of the caliphate, and on advocating the Rightly-Guided Caliphs in the wars of apostasy and their exit for jihad and participation in the Islamic conquests in all fields, and his supportive political position And the supporter of Ali bin Abi Talib.